Exploration of patient loyalty through value integration and customer satisfaction in class B university hospitals on Java Island - Sutrisno, Sutrisno; Andjarwati, Tri; Budiarti, Endah (Edelweiss Applied Science and Technology, 2024)
This study aims to analyze the relationship between accessibility, brand image, and service quality on customer value, customer satisfaction, and revisit intention at the University Hospital (RSPT). The main focus of the study is the mediating role of customer value and customer satisfaction in influencing patient loyalty. With a holistic approach, this study highlights the unique dynamics of RSPT that integrates education and health care functions. The findings indicate that accessibility and service quality have a significant influence on customer value, while brand image has a more limited contribution in this context. In addition, customer satisfaction plays an important role in bridging the relationship between customer value and revisit intention, making it a strategic dimension in increasing patient loyalty. A statistical approach using the SmartPLS method was carried out to evaluate the validity and reliability of the research model. The test results showed that the Average Variance Extracted (AVE) value of all constructs was greater than 0.50, reflecting that convergent validity was met. The Composite Reliability and Cronbach's Alpha values were each greater than 0.70, indicating good internal consistency. Discriminant Validity is assessed through the Heterotrait-Monotrait Ratio (HTMT) with a value of less than 0.85, ensuring clear differences between constructs. The results of the path analysis show that accessibility (X2) significantly affects customer value (Z) with a coefficient of 0.826 (T = 6.993, p < 0.000). Likewise, service quality (X3) has a positive effect on customer value with a coefficient of 0.291 (T = 2.521, p < 0.012). In contrast, brand image (X1) does not have a significant effect on customer value (coefficient -0.192, T = 1.783, p = 0.075). Customer value has a significant effect on customer satisfaction (coefficient 0.922, T = 55.068, p < 0.000), which in turn affects patient revisit intention (coefficient 0.922, T = 53.495, p < 0.000). This study provides theoretical contributions by expanding the healthcare management literature, especially in the unique context of RSPT. Practically, these findings recommend improving accessibility and service quality to enhance patient loyalty. This study also opens up opportunities for further research with a longitudinal approach to understand changes in patient perceptions over time.